The economic impact of early tooth loss in turkish children and adolescents - Ali Erdem; Ebru Baytaroğlu; Erhan Dilber; Mehmet Bilgin; Osman Ağlarcı (Cumhuriyet University, 2015)
Objectives: We sought to measure the financial burden on the Turkish government from early tooth loss and tooth impaction requiring prosthetics in 6-22-year-olds. Material and Methods: We evaluated 28784 teeth from 1028 patients (379 males and 649 females) between the ages of 6 and 22 and assessed the indications for prosthodontic treatment. As the study age range is not reliable for the presence of third molars, third molars were ignored. We divided the patients into pediatric and young adult groups. The homogeneity of data was evaluated with the Kolmogorov-Smirnov test. Differences between the genders and groups were evaluated with Pearson's Chi-squared test and the Mann-Whitney U-test.Results: Missing permanent teeth predominated in the young adult group (1.61) %, while impacted permanent teeth predominated in the pediatric group (0.81 %). Applying these rates to the population as a whole, 1.8 million pediatric and 6.2 million young adult cases of missing teeth may be extant in Turkey.Conclusion: Making dental hygiene information available to all socioeconomic groups would require an initial outlay of expenses, but savings would be realized both from preventing lost work and school time and from avoiding the need for prosthetic work in millions of Turkish citizens.